Urethral obstruction in dogs: diagnosis and management. Issue 1 (23rd January 2019) - Shales, Chris
Abstract : Urethral obstruction is not uncommon in dogs, particularly males. Obstruction can be either partial or complete and can result in a range of clinical signs according to the degree and duration of the condition. This article will review the diagnostic process and the options available for re‐establishing urine flow in the short and longer term.